Anti-hepatitis B virus active secoiridoids from Swertia kouitchensis - He, Kang (Springer Berlin Heidelberg, 2011)
Three new secoiridoids, swertiakoulactone (1) and swertiakosides A and B (2 and 3), were isolated from Swertia kouitchensis. Their structures were elucidated by comprehensive spectroscopic analyses including MS, IR, 1D and 2D NMR data. By the anti-hepatitis B virus (HBV) assay on Hep G 2.2.15 cells line in vitro, compound 1 showed moderate activities inhibiting the HBsAg secretion (IC(50) = 1.10 mM, SI = 4.39) and HBV DNA replication (IC(50) = 1.16 mM, SI = 4.12). [Image: see text]